Perbandingan Kemampuan Bahasa Arab Mahasiswa Alumni Pesantren Dengan Non-Pesantren Prodi Pendidikan Bahasa Arab Institut Agama Islam Negeri Parepare - H.N, nurkharisma (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2023)
The Arabic language education learning program at the Parepare State Islamic Institute has many enthusiasts from among students, alumni of Islamic boarding schools and non-Islamic boarding schools. It can be seen that pesantren alumni students are more likely to study Arabic than alumni students from non-Islamic boarding schools. This study was conducted to compare the Arabic language skills of pesantren alumni students with non-Islamic boarding schools in the Arabic language education learning program at the Parepare State Islamic Institute. This research uses ex post facto method with purposive sampling technique in taking the sample. From the results of this study, it was found that there was no significant difference between the Arabic language skills of pesantren and non-Islamic boarding school alumni students in the Arabic language education learning program at the Islamic Institute of Parepare.